A conceptual framework for the mediating effect of audit quality on the relationship between audit committee attributes and financial reporting quality - Bala, Hussaini; Amran, Noor Afza; Shaari, Hasnah (De La Salle University, 2019)
Prior studies have documented that the complementary functions of audit committees (ACs) with respect to audit quality (AQ) is complex and goes beyond a direct relationship. This paper aims to propose a framework consistent with the complementary hypothesis to show the mediating effect of AQ on the relationship between AC attributes and financial reporting quality (FRQ). To achieve this, we reviewed the literature regarding ACs, AQ, and FRQ and found that studies on AC and FRQ presented mixed results. We also found that there was little evidence regarding the influence of legal experts and AC public accounting expertise in ACs. Consequently, this warrants further research. There is a need for future studies to examine our proposed framework further. Future research should also explore the effects of internal audits and whistle-blowing policy on firms’ ACs and FRQ.